On the acoustics of installed subsonic jets - O'Reilly, Ciarán J. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2009)
The reduction of community exposure to aircraft noise is an important consideration in the design of future aircraft. A review is currently under way of novel aircraft configurations, which may exploit the fuselage, wings and empennage, as acoustic shields in order to reduce the engine noise transmitted towards the ground during take-off and approach. To assess the acoustic benefits attainable with such configurations, suitable design evaluation methodologies must firstly be developed. The complex physical noise sources must be represented in a manner appropriate : or input into propagation methods. In this thesis, the development of an innovative methodology to compute the reduction in the sound pressure level from a shielded jet configuration is described. Analyses centres on the European FP6 NACRE project’s wind-tunnel test programme, in which a simphfied jet shielding configuration was examined. Directional point sources are located from the mean flow properties of a Reynolds-averaged Navier-Stokes solution using a variation on Lighthill’s acoustic analogy.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin